Financial Shenanigans : A Case Study of Nigeria - Onitilo, Nnenna Chidimma (2015)
This study investigates the identified cases of financial shenanigans in between 2001 and 2009 in Nigeria. The scope of this study includes the identification of the common attempts and approaches used by companies and the motivations for financial shenanigans. A cross country comparison of the characteristics of the corporate reporting environments between Nigeria and Malaysia was also carried out. This study finds that the most common attempt used by the sample companies are majorly revenue overstatement and understating the expense accruals. Revenue and expenses are the major accounts which have a direct impact on the net income of a company and as a result, the main targets for manipulation. From the findings of this study, the motivations for financial shenanigans are external contract incentives, stock over pricing, closeness to contract covenants and management compensation contract incentives. From the cross country comparison between Nigeria and Malaysia, the findings show that board size and composition negatively affected the performance of firms in both countries. This is due to the fact that there is a high rate of family ownership of these companies and they exert dominant control of the board, rendering them inactive and in some cases, irrelevant. Thus in both countries, corporate governance should look beyond compliance, box- ticking and sign-off of the compliance requirements by the regulatory authorities and focus more on human capital training and developments which will promote honest and accurate financial reporting in both countries.